Dampak Pelatihan Tari terhadap Rasa Percaya diri Siswa di SMAN 4 Pariaman - Nashiwa Natania Salsabilla; Indrayuda Indrayuda (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study aims to find out how dance training has an impact on students' confidence at SMAN 4 Pariaman. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps to analyze data are data collection, data reduction, data presentation and data verification. The results of the study showed that there was an increase in students' confidence when participating in dance training in dance extracurricular activities at SMAN 4 Pariaman which was influenced by optimistic, objective and responsible indicators. From the optimistic indicator, it can be seen that students have more willingness and do certain activities, students when they get new material, they look very eager to try and practice it well. From the objective indicators of impartial, fair and open students, students are able to make good friends with anyone and are also able to be fair to their peers. And from the responsibility indicator, being able to complete the tasks given and keep the promises according to the agreement, students who have tasks given by their coach always complete them on time and always follow whatever directions the coach tells them to do. So it can be concluded that the dance training carried out is able to increase students' confidence.